The Impact of the Inflows of the Foreign Direct Investment on the Egyptian Economic Growth Rate - Time Series Analysis - Mohamed, Ghada; El-Deen, Eman Gamal El-Deen (Archives of Business Research, 2019)
This paper tests empirically the effect of the real inflows of the foreign direct investment on the Egyptian growth rate by utilizing a simple intervention time series model to capture the dynamism of such effect over time. The results show positive significant effects of the real foreign direct investment inflows on the Egyptian growth rate but recommendations show that this effect should be enhanced from time to time in order to prolong the convergence to the saddle path of the growth and hence to guarantee a sustainable growth over-time.